TiO2 quantum dots/reduced graphene oxide composite modified with Au for electrochemical oxidation reaction. (5th May 2022) - Yu, Jiage; He, Lihua; You, Jia; Huang, Lanlan; Shu, Honghui; Zhang, Bingqing
Abstract: TiO2 /graphene as catalyst substrate has attracted considerable attentions in the field of electrochemistry because of the synergistic effects bring from good chemical stability of TiO2 and intrinsic superior conductivity of graphene. In this work, TiO2 quantum dots are prepared on reduced graphene (TiO2 QDs/RGO) by a novel supercritical CO2 fluid assisted hydrothermal method, following, the Au–TiO2 QDs/RGO electrodes are achieved by electrodepositing Au on the TiO2 QDs/RGO support. The obtained Au–TiO2 QDs/RGO shows better electrocatalytic activity for glucose oxidation than the electrodes of Au-RGO, Au–P25 (commercial TiO2 ) and Au-Mixed P25/RGO. Specially, the lower the loading of Au, the more significant in performance of Au–TiO2 QDs/RGO distinguishes from other three electrodes. The high activity is probably owing to the synergistic catalytic effects of TiO2 QDs and Au, the quantum-sized TiO2 QDs, as well as the co-substrate of RGO. All of these are beneficial to electron transfer and the release of poisoning intermediates thus promote the electrocatalytic oxidation of glucose. The study might offer some new clues for designing efficient hybrid catalysts in applications of electrocatalysis and energy conversion/storage. Highlights: Au NPs supported on TiO2 QDs/RGO shows excellent activity for glucose oxidation. TiO2 QDs are prepared by a novel supercritical CO2 fluid assisted hydrothermal method. The activity of Au–TiO2 QDs/RGO is much better than Au-RGO, Au–P25, Au- Mixed P25/RGO. Owing to the synergistic catalytic effect of TiO2 QDs and Au, the quantum-size of TiO2, and the co-substrate of RGO.